Counseling and Examination of Sharp Vision for Presbyopia Screening (Old Eyes) and Provision of Reading Glasses to the Elderly at Tresna Werdha Social Institution Bengkulu Province - Suryani, Utari Hartati; Zainuddin, Zayadi (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2023)
According to World health Organization (WHO), the age group >60 years is categorized as elderly (elderly). Normally with age, a decrease in organ function will also occur naturally, one of which is in the organs of vision. So far, the community considers the decline in the function of vision in the elderly group as a normal thing to happen and does not require routine checks. Even though this condition will increase the risk of falling in the elderly and can cause other complex problems. The social institution is a place that aims to accommodate the elderly so that they can live their old age in a more quality manner, the Tresna Werdha Social Institution is one example and is under the guidance of the Social Service of Bengkulu Province which accommodates quite a number of elderly as its fostered citizens with various existing health problems, One of them is the problem of decreased visual acuity. In view of the conditions above, then community service needs to be done in this place, such as counseling, visual acuity checks and providing reading glasses to the elderly at the Tresna Werdha Bengkulu social institution. The purpose of this activity is to improve the quality of life for the elderly and reduce the risk of falling, especially for the assisted residents of the Tresna Werdha Social Institution, Bengkulu Province. The result of this activity was that 43 elderly people took part in educational activities, visual acuity checks and the provision of reading glasses which were carried out on October 2, 2022 by a community service team from the Faculty of Medicine and Health Sciences, University of Bengkulu. From this activity, it was found that 21 elderly people (49%) received assistance in the form of reading glasses while 22 (51%) other elderly people could not receive assistance in the form of reading glasses because they had cataracts.